PHOSPHATE LU-HF GEOCHRONOLOGY - Barfod G.H.; Otero O.; Albarède F. (My University, 2003)
Igneous, metamorphic and biogenic apatite contains Lu and Hf in proportions that make this mineral suitable for dating by the 176Lu–176Hf method. We present a new method for separation of Lu and Hf from apatite that involves a single extraction column step for Hf and a second exchange column step for Lu. This procedure allows rapid sample processing prior to analysis by MC-ICP-MS. Results from the igneous Gardiner, Skaergaard and Khibina Intrusions indicate that the closure temperature for the Lu–Hf isotopic system in apatite is relatively high. The Lu–Hf isochron age of f60 Ma for the Skaergaard Intrusion, East Greenland, is older than the generally accepted emplacement age, but does not appear to be a product of mixing. A centimetersized apatite from the Otter Lake area, Grenvillian Province, yields high and variable 176Lu/177Hf ratios showing that metamorphic apatite may, in some cases, allow for mono-mineral dating. The most important application of the method is undoubtedly its potential use for dating sedimentary formations. Although we find biogenic apatite in porous matrix highly susceptible to post-depositional resetting of the Lu–Hf isotopic system, the preservation of a near-depositional age for a shark tooth from the impermeable London Clay and recent work on crystalline authigenic phosphorites [Earth Planet. Sci. Lett. 201(2002) 203] show the Lu–Hf system to be a promising tool for direct dating of sedimentary formations.